Optimalisasi Layanan RT/RW dengan Memanfaatkan Teknologi Informasi Berbasis IoT - Solikhin; Martono (Politeknosains, 2019)
In the area of Meteseh Village, Tembalang District, there is RW XXIX which is located in the Graha Mulia Asri (GMA) III housing complex which is in charge of 5 (five) RT. Neighborhood RW XXIX The GMA III housing estate is classified as new, the area is quite large and has a relatively dense population. The current condition is the problem that is often faced by RT and RW heads in carrying out their main duties and functions (tupoksi), namely in serving their citizens related to various administrative requirements less than optimal, due to one side being unable to leave their rights in carrying out their activities as individuals and heads families so that services to their citizens cannot be ontime but only at certain times, conditions like this clearly have an impact on impeded smoothness in carrying out the tasks of the village or village government in development and society. In addition, in providing important information / news to its citizens, it is also waiting for routine community meeting every month. In an effort to carry out its duties, functions and to organize its environment, RT V RW XXIX housing GMA III needs to make changes and breakthroughs. One of them is the need for support in the use of information technology to help, manage and manage their tasks in order to improve services to the community. In this study he made an IoT-based RT Management Information System to optimize its services.